Analysis of Potential Landslides Using Geographic Information System (GIS) on Rail Tunnel in Gunung Gajah Village, Lahat Regency of South Sumatra - Mirza Adi Warman; Muhammad Taufik Toha; Endang Wiwik Dyah Hastuti (Science and Technology Indonesia, 2018)
Lahat Regency is one of the cities which is prone to geological disasters such as landslides. The landslide is caused by a varied topography such as flat, hilly or mountainous. On January, 23rd 2016, the landslide occurred on the mouth of a railway tunnel in Gunung Gajah Village, Lahat Regency. The purpose of this study is to determine the influence of geological factor on the slope stability. The method of research is a survey method based on geographic information systems in the form of interpretation and analysis of the causes and triggers of landslides with a direct approach in the field by doing scoring an overlay technique. The analysis obtained the parameters of landslides such as: slope, lithology/physical properties of rocks, geological structure and land use. The results and conclusions of this research are the landslide potential distribution map in Gunung Gajah Village, Lahat Regency consisting of three classes of landslide vulnerability: low, medium and high and in the focus areas of research entering the high level of vulnerability.